Hydrogen Peroxide-Induced Oxidative Damage in Human Chondrocytes: The Prophylactic Effects of Hypericum Perforatum Linn Extract on Deoxyribonucleic acid Damage, Apoptosis and Matrix Remodeling by a Disintegrin-Like and Metalloproteinase With Thrombospondin Motifs Proteinases - Sümeyya AKYOL; Yunus YÜKSELTEN; Özlem ÇAKMAK; Veli UĞURCU; Aynur ALTUNTAŞ; Mukaddes GÜRLER; Ömer AKYOL; Kadir DEMİRCAN1 (Archives of Rheumatology, 2014)
Objectives: This in vitro study aimed to examine the protective roles of Hypericum perforatum Linn (HPL) extract on cell viability, DNA damage, apoptosis and a disintegrin-like and metalloproteinase with thrombospondin motifs (ADAMTS) proteins in chondrocytes induced by hydrogen peroxide (H2O2), as a model of chondrocytes subjected to reactive oxygen species (ROS) attack in rheumatoid arthritis and osteoarthritis. Materials and methods: Human chondrosarcoma cell line (OUMS-27) was used. Cells were incubated with different concentrations of methanolic extract (100, 400, and 750 μg/ml) of HPL for 36 hours, and then treated with 0.7 mM H2O2 for two hours. Trypan blue was used for evaluation of cell viability, while DNA damage was evaluated by alkaline Comet assay. Caspase-1, ADAMTS5, ADAMTS9, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) proteins were analyzed by Western blot. Results: In vitro H2O2 treatment decreased OUMS-27 cell viability. Cells pretreated with HPL at concentration of 400 μg/mL were best protected from H2O2 toxicity. Compared to 100 μg/ml concentration, pretreatment of cells with 750 or 400 μg/ml of HPL generated more protection against H2O2-induced DNA damage. Hydrogen peroxide application to the cells led to a slight increase in Caspase-1 expression, which shows no apoptosis. The most prominent increase in Caspase-1 level was shown in cells treated with 400 μg/ml of HPL extract. There was an increase in ADAMTS9 and a decrease in ADAMTS5 levels upon H2O2 administration. Pretreatment with HPL led to more decrease in ADAMTS5 level, indicating the protection of extracellular matrix attacked by these proteinases in cartilage tissue. Conclusion: It can be concluded that HPL has a potential to reverse the negative effects and processes induced by H2O2 in OUMS-27 cells and it can protect the surrounding cartilage area of chondrocytes from oxidative damage, which is suggested to be one of the main molecular factors accused for progression of rheumatoid arthritis and osteoarthritis.